2005
DOI: 10.1007/s00467-005-1988-4
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and urine nitric oxide levels in healthy Turkish children

Abstract: Nitric oxide (NO) is an important messenger molecule with a wide range of actions in virtually all cell systems and organs. In kidneys it participates in glomerular and medullary hemodynamics, tubuloglomerular feed-back, renin secretion, and extracellular fluid balance. Although the role of NO in regulating renal function in adults is well-established, it has recently been suggested that NO has a more critical role in maintaining basal renal blood flow and glomerular filtration rate (GFR) in the developing kid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 16 publications
2
9
0
Order By: Relevance
“…This finding agrees with other independent research groups who reported high levels of urinary nitrate excretion (index of NO synthesis) in infancy that declined with age (35)(36)(37). A similar age-related decrease was also observed in plasma (6,37) and cerebrospinal fluid nitrate concentrations (38). Furthermore, analyzing the data presented in a previous study of convalescent, treated newborns with pulmonary hypertension (5) 15 N]nitrate enrichments in the range of 0.5%-1.2% with mass spectrometry.…”
Section: Subjectssupporting
confidence: 93%
See 1 more Smart Citation
“…This finding agrees with other independent research groups who reported high levels of urinary nitrate excretion (index of NO synthesis) in infancy that declined with age (35)(36)(37). A similar age-related decrease was also observed in plasma (6,37) and cerebrospinal fluid nitrate concentrations (38). Furthermore, analyzing the data presented in a previous study of convalescent, treated newborns with pulmonary hypertension (5) 15 N]nitrate enrichments in the range of 0.5%-1.2% with mass spectrometry.…”
Section: Subjectssupporting
confidence: 93%
“…However, multiple regression analysis showed age as the only predictor variable of whole-body NO synthesis, suggesting that normal aging modulates NO homeostasis in children. This finding agrees with other independent research groups who reported high levels of urinary nitrate excretion (index of NO synthesis) in infancy that declined with age (35)(36)(37). A similar age-related decrease was also observed in plasma (6,37) and cerebrospinal fluid nitrate concentrations (38).…”
Section: Subjectssupporting
confidence: 92%
“…Recent findings have suggested that endothelial injury acts as a primary event leading to renal hypoxia with disturbances in NO pathways playing a major role (12). Studies have suggested that these metabolites may be useful markers of endogenous NO synthase activity (17). Thus, diminished urinary nitrate in patients with early AKI may reflect diminished endothelial production of NO and suggests targeting the NO pathway as a means to treat or prevent the development of AKI.…”
Section: Discussionmentioning
confidence: 99%
“…However, a negative correlation of NOx with age was found in controls but not in DS. It has been reported that the tendency of urinary nitrate levels to decrease with age in healthy children may be a reflection of an age-related increase in GFR (Elli et al, 2005), so GFR could be impaired in DS.…”
Section: H 2 Omentioning
confidence: 99%